Pengaruh palm kernel oil terhadap karakteristik daging panggang meltique: pH, susut masak, dan tingkat kesukaan - Dainy, Nunung Cipta; Apriantini, Astari; Humayrah, Wardina; Seftiyani, Khori; Aditia, Edit Lesa (Poltekkes Kemenkes Aceh, 2024)
Background: Beef has the highest Digestible Indispensable Amino Acid Score. However, beef is often difficult to consume because it has a tougher texture than poultry or fish. Meltique beef can be an alternative beef product that is easy to consume, but it still uses imported vegetable oil, which has an impact on the high selling price. It is necessary to innovate meltique using local vegetable oil.Objective: Analyse the effect of palm kernel oil (PKO) addition on the pH, cooking shrinkage and palatability of meltique meat.Methods: Using a Completely Randomised Design conducted at the Laboratory of the Faculty of Animal Husbandry, IPB from April to June 2024. The beef used was Brahman Cross sirloin. Two PKO formulas were injected, MP1 and MP2. There were four controls, namely MK1, MK2, WG and DR. The variables studied were pH using a pH meter, cooking loss by calculating the difference in raw-cooked weight, and the level of panellist preference using the hedonic test form. There were 25 semi-trained panelists who met the inclusion criteria to rate the level of preference for nine sensory attributes with a score range of 1 - 5. Statistical tests used ANOVA to analyse differences in pH, cooking loss, and Kruskal-Wallis test to analyse differences in level of preference.Results: There was a significant difference in the pH values of MP1 and MP2 with WG (P-value =0.000). There was no difference in cooking loss value (p-value =0.220). Hedonic test results showed that the level of preference of MP1 and MP2 was significantly different from WG (p-value <0.05).Conclusion: Meltique beef formulas have standard pH characteristics and cooking loss values similar to wagyu beef, but the preference level is still different from wagyu beef.